Sales leadership : the essential leadership framework to coach sales champions, inspire excellence, and exceed your business goals - Rosen, Keith (John Wiley & Sons, Inc., 2018)
"Coaching is the universal language of learning, development and change." style="color: #333333; font-family: Arial, sans-serif; font-size: 14px;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px;" />Imagine a workplace without fear, stress or worry. Instead, you're acknowledged as a valued, contributing team player who doesn't sacrifice priorities, values, happiness or your life for your job. Sound ludicrous' Consider this is a reality in many thriving organizations. style="color: #333333; font-family: Arial, sans-serif; font-size: 14px;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px;" />Most leadership books don't apply to sales leadership. Sales leaders are uniquely and indispensably special and need to be coached in a way that's aligned with their role, core competencies, and individuality to achieve their personal goals and company objectives. style="color: #333333; font-family: Arial, sans-serif; font-size: 14px;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px;" />What if you can successfully coach anyone in 15, 5 or even 60 seconds using one question'>'Sales Leadership makes delivering consistent, high-impact coaching easy. For busy, caring managers, this removes the pressure and misconception that, "Coaching is difficult, doesn't work, and I don't have time to coach." style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" />Since most managers don't know how to coach, they become part of the non-stop, problem-solving legion of frustrated Chief Problem Solvers who habitually do other's work, create dependency and nourish the seed of mediocrity. style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" />Great business leaders shift from doing people's job to developing them by learning the language of leadership - coaching. style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" />In its powerful simplicity, Sales Leadership delivers a chronological path to develop a thriving coaching culture and into a coaching leader who develops top performing teams and sales champions. style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" />Using Keith's intuitive'LEADS Coaching Framework, 'the coaching talk tracks for critical conversations, and his Enrollment strategy to create loyal, unified teams - you will inspire immediate change. Now, coaching is easily woven into your daily conversations and rhythm of business so that it becomes a natural, healthy habit. style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" /> style="color: #333333; font-family: Arial, sans-serif; font-size: 14px; text-decoration: underline;" />In his award-winning book, 'Coaching Salespeople Into Sales Champions>, Keith was the first Master Certified Coach to share his person.